2008
DOI: 10.1002/hipo.20462
|View full text |Cite
|
Sign up to set email alerts
|

Absence of carboxypeptidase E leads to adult hippocampal neuronal degeneration and memory deficits

Abstract: Molecules that govern the formation, integrity and function of the hippocampus remain an important area of investigation. Here we show that absence of the proneuropeptide processing enzyme, carboxypeptidase E (CPE) in CPE knock-out (KO) mice had a profound effect on memory, synaptic physiology and the cytoarchitecture of the hippocampus in these animals. Adult CPE-KO mice displayed deficits in memory consolidation as revealed by the water-maze, object preference and social transmission of food preference tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 26 publications
(37 reference statements)
1
76
0
1
Order By: Relevance
“…All animal work was performed with the approval of the animal care and use committee (ACUC) of NICHD. Cell death induction of the cultured cells was performed as previously described (Woronowicz et al 2008). In brief, AtT-20 cells and cerebral cortical cultures were treated with 50 μM hydrogen peroxide in the presence or absence of serpinin or pGlu-serpinin for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…All animal work was performed with the approval of the animal care and use committee (ACUC) of NICHD. Cell death induction of the cultured cells was performed as previously described (Woronowicz et al 2008). In brief, AtT-20 cells and cerebral cortical cultures were treated with 50 μM hydrogen peroxide in the presence or absence of serpinin or pGlu-serpinin for 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, CPE KO mice display memory deficits as revealed by the Morris water maze, object preference, and social transmission of food preference [17] , and show no evoked long-term potentiation (which is required for memory and learning) in hippocampal slices. Neonatal CPE KO mice also exhibit a significant delay in eye opening, which reflects a developmental delay in the central nervous system (Cawley et al ., unpublished data).…”
Section: Cpe Knock-out Mice Have Neurological Deficitsmentioning
confidence: 99%
“…In addition, Cpe fat/fat mutant mice lacking CPE exhibit anxiety- and/or depression-like behaviors [18] . CPE KO mice at 4 weeks of age or older, but not at 3 weeks, exhibit marked degeneration of the CA3 region which normally expresses high levels of CPE [17] . The neurodegeneration in CPE KO mice was initially thought to be a developmental defect.…”
Section: Cpe Knock-out Mice Have Neurological Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, calbindin staining showed early termination of the mossy fibers before reaching the CA1 region in the hippocampus of CPE −/− mice. Ex vivo studies revealed that apoptosis of primary cultured rat hippocampal neurons induced by hydrogen peroxide, a reactive oxygen species (ROS), was dramatically suppressed when CPE was overexpressed in these cells (Woronowicz et al 2008). These findings indicate that CPE is essential for survival of CA3 neurons and maintenance of hippocampal mossy fiber morphology as well as function, including consolidation of memory.…”
mentioning
confidence: 96%